Some peculiarities of triplet excitations dynamics in organic macromolecules and crystals. Issue 1 (2nd November 2022) - Yashchuk, V. M.; Galunov, M. Z.; Lebedyeva, I. V.; Tarasenko, O. A.; Navozenko, O. M.; Vashchilina, E. V.; Krech, A. V.; Losytskyy, M. Yu.; Dotsenko, M. A.
Abstract: Spectral properties of polymer macromolecules in the optical energy range and relation of these properties to the chemical structure and energy levels system of polymers were examined. The nature of optical centers of the macromolecules with π-electron systems localized on separate groups (so-called chromophores) was analyzed. It was stressed that such vitally important biopolymers as DNA and RNA belong to this type of polymers. It was shown that in synthetic and biological macromolecules with pendant aromatic groups, the triplet excitons meet and annihilate with the very high probability due to large lifetime and one-dimensional motion. The presented results prove that efficiency of triplet-triplet annihilation processes (at the used excitation power) is higher than efficiencies of other electronic processes. Consideration of this fact in the kinetic equation for triplet excitons in macromolecule leads to inverse square root dependence of phosphorescence intensity on the macromolecule length. At the same time, for three-dimensional molecular crystals of stilbene and para-terphenyl, the intensity of the delayed fluorescence is less dependent on the size of the granules compared to the dependence of the delayed fluorescence intensity on the length for one-dimensional macromolecules.